1984
DOI: 10.1038/ki.1984.73
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid and bone response of the diabetic patient to uremia

Abstract: Biochemical and radiologic indices of bone disease were assessed in 26 insulin-dependent diabetic patients and 28 nondiabetic patients with endstage kidney disease. The two groups were comparable in age, sex, duration of renal failure, and length of time on dialysis. Diabetic patients showed significantly lower serum calcium and immunoreactive parathyroid hormone (iPTH) levels than nondiabetic patients. iPTH was not related to total serum calcium, but was positively correlated with serum phosphorous (r = 0.37,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
34
0
1

Year Published

1986
1986
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(36 citation statements)
references
References 25 publications
1
34
0
1
Order By: Relevance
“…It has been reported by others that diabetic ESRD patients may have lower PTH levels than their nondiabetic counterparts and may be more susceptible to low-turnover bone disease (10,11). High-dose parenteral vitamin D is often attempted as a "final" nonsurgical strategy when parathyroidectomy is being considered (12).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported by others that diabetic ESRD patients may have lower PTH levels than their nondiabetic counterparts and may be more susceptible to low-turnover bone disease (10,11). High-dose parenteral vitamin D is often attempted as a "final" nonsurgical strategy when parathyroidectomy is being considered (12).…”
Section: Discussionmentioning
confidence: 99%
“…Studies exploring SHPT in patients with CKD have characterized the physiologic factors governing the relationship between PTH level and other components of bone and mineral metabolism, such as calcium, phosphorus, and vitamin D, mostly in the context of alterations in these factors occurring as a function of the level of severity of CKD (11)(12)(13)(14)(15)(16). There is indication from populations without CKD that PTH levels are also influenced by various demographic (17,18), anthropometric (19), and comorbidity characteristics (20). Knowledge of such associations in patients with CKD is important, because effect modification by clinical characteristics of SHPT in CKD may have therapeutic and prognostic implications.…”
mentioning
confidence: 99%
“…et al, 1987;Pei, Y. et al, 1993), which may be related to a lower bone turnover rate, which has been reported in type 1 diabetics before the onset of clinical renal disease (Andress, D.L. et al, 1987;Vincenti, F. et al, 1984). Therefore, because of the sometimes similar clinical manifestations of hyperparathyroidism and aluminum overload, physicians treating dialysis patients with hyperparathyroidism should consider the possibility of concurrent aluminum problems, especially in high-risk diabetic patients.…”
Section: Managing Aluminum Overload In Dialysis Patients With Hyperpamentioning
confidence: 99%